1985
DOI: 10.1177/001440298505200209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Role, Gender, Age, and Parental Status on Perception of Childhood Problems

Abstract: Effects of rater characteristics (role, gender, age, and parental status) on ratings of childhood problems were investigated. Four groups of raters were included: clinical psychologists, school psychologists, teachers, and parents. Ail raters evaluated the psychological importance of the 118 items comprising the Child Behavior Checklist developed by Achenbach and Edelbrock. A discriminant function analysis provided strong evidence that role groups could be differentiated on the basis of ratings. One-way analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1989
1989
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previous research (e.g, Marsh, Stoughton, & Williams, 1985) has suggested that perceptions of a child's behavior vary greatly according to group membership. The present study reiterates and reinforces the point.…”
Section: Results and Discussonmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research (e.g, Marsh, Stoughton, & Williams, 1985) has suggested that perceptions of a child's behavior vary greatly according to group membership. The present study reiterates and reinforces the point.…”
Section: Results and Discussonmentioning
confidence: 99%
“…Although there is literature to suggest that characteristics of the rater influence perception of children's problems (Marsh, Stoughton, & Williams, 1985), little work has actually been done with parents.…”
mentioning
confidence: 99%
See 1 more Smart Citation